POTENSI ANTIOKSIDAN METABOLIT SEKUNDER FRAKSI ETIL ASETAT DARI KULIT BATANG EBONI (Diospyros celebica Bakh.) - Vivi Sasmita; Ahmad Ridhay; Hardi Ys (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2019)
Research on the antioxidant potential of the secondary metabolite compound, ethyl acetate from ebony bark (Diospyros celebica Bakh.) has been conducted. This study aims to characterize and determine the antioxidant activity of secondary metabolites of ethyl acetate fraction from ebony bark. Ethyl acetate extract was fractionated using Liquid Vacum Chromatography (KVC) and Gravity Column Chromatography (KKG). The isolated compounds were characterized using UV-Vis and IR spectrophotometers. Data on maximum absorption of λmax 273 nm from UV-Vis analysis showed the presence of chromophore phenol. IR spectral data showed several specific peaks, among others, at wave number (ʋ) of 3425.58 cm-1 indicating the presence of –OH group, C-H aliphatic bond at ʋ of 2924.09 cm-1 and 2854.65 cm-1, and the peak at ʋ of 1604.77 -1465.90 cm-1 and 3078.39 cm-1 indicated the aromatic group, reinforcing the assumption that the isolates produced were phenolic compounds. IC50 value of 75.47 µg/mL from antioxidant activity testing showed that the isolates obtained were antioxidant compounds with strong antioxidant categories. Keywords: antioxidant, Diospyros, ebony, phenolic, isolation